CEFTRIAXONE BLOCKS THE POLYMERIZATION OF Α-SYNUCLEIN AND EXERTS NEUROPROTECTIVE EFFECTS IN VITRO - Vidhya, G.; Anitha, J.; Yadav, A Santhosh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The β-lactam antibiotic ceftriaxone was suggested as a therapeutic agent in several neurodegenerative disorders, either for its ability to counteract glutamate-mediated toxicity, as in cerebral ischemia, or for its ability to enhance the degradation of misfolded proteins, as in Alexander’s disease. Recently, the efficacy of ceftriaxone in neuroprotection of dopaminergic neurons in a rat model of Parkinson’s disease was documented. However, which characteristics of ceftriaxone mediate its therapeutic effects remains unclear. Since, at the molecular level, neuronal α-synuclein inclusions and pathological α-synuclein transmission play a leading role in initiation of Parkinson-like neurodegeneration, we thought of investigating, by circular dichroism spectroscopy, the capability of ceftriaxone to interact with α- synuclein. We found that ceftriaxone binds with good affinity to α-synuclein and blocks its in vitro polymerization. Considering this finding, we also documented that ceftriaxone exerts neuroprotective action in an in vitro model of Parkinson’s disease. Our data, in addition to the findings on neuroprotective activity of ceftriaxone on Parkinson-like neurodegeneration in vivo, indicates ceftriaxone as a potential agent in treatment of Parkinson’s disease.